Bhutanese Older Adult Refugees Recently Resettled in the United States: A Better Life With Little Sorrows. (March 2018) - Gautam, Ramraj; Mawn, Barbara E.; Beehler, Sarah
Purpose: This study explores the experiences and adjustment process among older Bhutanese refugees resettled in the United States and identifies their unmet health and social service needs.Design: This phenomenological study design included the conduction of nine in-depth semistructured interviews in the respondents' native language. The researchers adhered to the steps outlined by Moustakas for data analysis.Results: The five identified themes included the following: a better life but with little sorrows, cultural tensions related to adaptation, language as a barrier to success in the United States, isolation and loneliness, and worries about citizenship and its impact on the future.Discussion/Implications for Practice: Psychological adjustment to life in the United States can have profound impact on the health of Bhutanese older adults. Nurses and health care providers should integrate culturally congruent health care, raise awareness of the unique needs, and advocate for policy changes that will benefit this group of older adult refugees whose lives have frequently been upended.